Geologic and Structural Evolution of the NE Lau Basin, Tonga: Morphotectonic Analysis and Classification of Structures Using Shallow Seismicity - Anderson, Melissa O.; Norris-Julseth, Chantal; Rubin, Kenna Harmony; Haase, Karsten; Hannington, Mark D.; Baxter, Alan T.; Stewart, Margaret S. (Frontiers in Earth Science, 2021)
The transition from subduction to transform motion along horizontal terminations of trenches is associated with tearing of the subducting slab and strike-slip tectonics in the overriding plate. One prominent example is the northern Tonga subduction zone, where abundant strike-slip faulting in the NE Lau back-arc basin is associated with transform motion along the northern plate boundary and asymmetric slab rollback. Here, we address the fundamental question: how does this subduction-transform motion influence the structural and magmatic evolution of the back-arc region? To answer this, we undertake the first comprehensive study of the geology and geodynamics of this region through analyses of morphotectonics (remote-predictive geologic mapping) and fault kinematics interpreted from ship-based multibeam bathymetry and Centroid-Moment Tensor data. Our results highlight two notable features of the NE Lau Basin: (1) the occurrence of widely distributed off-axis volcanism, in contrast to typical ridge-centered back-arc volcanism, and (2) fault kinematics dominated by shallow-crustal strike slip-faulting (rather than normal faulting) extending over ~120 km from the transform boundary. The orientations of these strike-slip faults are consistent with reactivation of earlier-formed normal faults in a sinistral megashear zone. Notably, two distinct sets of Riedel megashears are identified, indicating a recent counter-clockwise rotation of part of the stress field in the back-arc region closest to the arc. Importantly, these structures directly control the development of complex volcanic-compositional provinces, which are characterized by variably-oriented spreading centers, off-axis volcanic ridges, extensive lava flows, and point-source rear-arc volcanoes that sample a heterogenous mantle wedge, with sharp gradients and contrasts in composition and magmatic affinity. This study adds to our understanding of the geologic and structural evolution of modern backarc systems, including the association between subduction-transform motions and the siting and style of seafloor volcanism.